The impact of anaerobic digestate on soil life: a review - van Midden, Christina; Harris, Jim A.; Shaw, Liz; Sizmur, Tom; Pawlett, Mark (Elsevier, 2023)
Using organic amendments to fertilise crops is a crucial part in the sustainability of agricultural systems. The residual slurry remaining after biogas production (anaerobic digestate) contains a rich source of plant nutrients that provides an alternative to mineral fertilisers. The delivery of many nutrients to plants is facilitated by a healthy soil biota: free-living and symbiotic microflora (e.g. archaea, bacteria and fungi) mineralize, solubilize and facilitate plant uptake of nutrients and the soil fauna (e.g. protozoa, microarthopods and earthworms) influence nutrient cycling processes as higher-level consumers and litter transformers. The delivery of nutrients to plants via the activity of this soil food web is influenced by fertiliser inputs. Here we review the impact of anaerobic digestate on soil biota. The quantity and composition of the carbon in digestate has a large influence on soil heterotrophic microbial dynamics and their subsequent influence on nutrient bioavailability. The main points are (1) digestate low in carbon has little effect on soil microorganisms, whereas digestate higher in carbon increases soil microbial abundance and diversity; (2) labile carbon stimulates fast-growing bacteria, whereas recalcitrant carbon shifts the microbial community in favour of slower-growing fungi and Gram-positive bacteria; and (3) earthworms, springtails and nematodes dwelling in the soil surface layer can be negatively affected by digestate application due to toxicity when compounds such as ammonia are present in high concentrations. Generalized understanding of the effect by digestates on soil biota is made difficult by differences in digestate properties caused by varying feedstock and production methods and the inherent heterogeneity of soil. There is a lack of research investigating the impact of repeated digestate application on soil biota and subsequently soil health. This information would give end users more confidence to substitute mineral fertilisers with digestate.
Keywords: Biogas residue; Soil organic matter; Soil microorganisms; Springtails; Earthworms; Sustainable fertilisation